Teachers' Role and the Development of Curriculum - Florencia Ananda Gulo (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This paper explores the key role of teachers in educational curriculum development, especially in the implementation and evaluation of curriculum design. Teachers' skills and knowledge are not only as curriculum implementers, but also as learning architects who influence students' learning experiences. Teachers not only master open material, but also have an important role in planning relevant and interesting learning activities. This paper highlights the important collaboration between teachers and other stakeholders, such as curriculum administrators, parents, and the educational community. This collaboration is the basis for creating a curriculum that is effective, responsive to student needs, and reflects various perspectives. By introducing the role of teachers in curriculum implementation and evaluation, this paper encourages appreciation of their contribution in shaping the direction of education. Effective collaboration and a deep understanding of teacher involvement are expected to increase the holism of curriculum development, create more meaningful learning experiences for students, and improve the overall quality of education..